HbA1c levels in non-diabetic older adults – No J-shaped associations with primary cardiovascular events, cardiovascular and all-cause mortality after adjustment for confounders in a meta-analysis of individual participant data from six cohort studies. Issue 1 (December 2016) - Schöttker, Ben; Rathmann, W.; Herder, C.; Thorand, B.; Wilsgaard, T.; Njølstad, I.; Siganos, G.; Mathiesen, E.; Saum, K.; Peasey, A.; Feskens, E.; Boffetta, P.; et al.
Abstract Background To determine the shape of the associations of HbA1c with mortality and cardiovascular outcomes in non-diabetic individuals and explore potential explanations. Methods The associations of HbA1c with all-cause mortality, cardiovascular mortality and primary cardiovascular events (myocardial infarction or stroke) were assessed in non-diabetic subjects ≥50 years from six population-based cohort studies from Europe and the USA and meta-analyzed. Very low, low, intermediate and increased HbA1c were defined as <5.0, 5.0 to <5.5, 5.5 to <6.0 and 6.0 to <6.5 % (equals <31, 31 to <37, 37 to <42 and 42 to <48 mmol/mol), respectively, and low HbA1c was used as reference in Cox proportional hazards models. Results Overall, 6, 769 of 28, 681 study participants died during a mean follow-up of 10.7 years, of whom 2, 648 died of cardiovascular disease. Furthermore, 2, 493 experienced a primary cardiovascular event. A linear association with primary cardiovascular events was observed. Adjustment for cardiovascular risk factors explained about 50 % of the excess risk and attenuated hazard ratios (95 % confidence interval) for increased HbA1c to 1.14 (1.03–1.27), 1.17 (1.00–1.37) and 1.19 (1.04–1.37) for all-cause mortality, cardiovascular mortality and cardiovascular events, respectively. The six cohorts yielded inconsistent results for the association of very low HbA1c levels with the mortality outcomes and the pooled effect estimates were not statistically significant. In one cohort with a pronounced J-shaped association of HbA1c levels with all-cause and cardiovascular mortality (NHANES), the following confounders of the association of very low HbA1c levels with mortality outcomes were identified: race/ethnicity; alcohol consumption; BMI; as well as biomarkers of iron deficiency anemia and liver function. Associations for very low HbA1c levels lost statistical significance in this cohort after adjusting for these confounders. Conclusions A linear association of HbA1c levels with primary cardiovascular events was observed. For cardiovascular and all-cause mortality, the observed small effect sizes at both the lower and upper end of HbA1c distribution do not support the notion of a J-shaped association of HbA1c levels because a certain degree of residual confounding needs to be considered in the interpretation of the results.